Ekranisasi Novel A: Aku, Benci dan Cinta Karya Wulanfadi ke Film A: Aku, Benci dan Cinta Karya Sutradara Rizki Balki - Dewi, Mona Lisa; Pangesti, Nesa Riska (TSAQOFAH, 2026)
This study is motivated by the need for a more in-depth examination of the changes that occur in the process of adapting literary works into film, with a specific focus on the adaptation of the novel A: Aku, Benci dan Cinta by Wulanfadi (print edition 2015) into the film A: Aku, Benci dan Cinta directed by Rizki Balki (released 2017). The study aims to analyze the forms of change from novel to film using ecranisation theory, which comprises three main aspects—reduction, addition, and varied modification—applied to the elements of plot, character and characterization, and setting. A qualitative descriptive method was employed, with data consisting of textual sequences obtained through close reading of the novel and detailed observation of the film as the objects of analysis. The findings show that, for the reduction aspect, 74 instances were identified in the plot, 17 in characters and characterization, and 4 in setting; for the addition aspect, 13 instances were found in the plot, 5 in characters and characterization, and 2 in setting; and for the varied modification aspect, 21 instances were identified in the plot, 10 in characters and characterization, and 4 in setting. These results indicate that the ecranisation of A: Aku, Benci dan Cinta into film involves a fairly intensive strategy of reduction, addition, and variation, particularly in the plot element, thereby producing a narrative structure that is more compact and aligned with the demands of the cinematic medium. This study contributes to the growing body of research on ecranisation and provides an empirical basis for comparative analyses between literary works and their film adaptations.